In situ assessment of the brain microcirculation in mechanically-ventilated rabbits using sidestream dark-field (SDF) imaging - Sitina, M; Turek, Z; Pařízková, R; Cerný, V (Physiological research, 2011)
Assessment of the cerebral microcirculation by on-line visualization has been impossible for a long time. Sidestream dark-field (SDF) imaging is a relatively new method allowing direct visualization of cerebral surface layer microcirculation using hand-held probe for direct contact with target tissue. The aim of this study was to elucidate the feasibility of studying the cerebral microcirculation in situ by SDF imaging and to assess the basic cerebral microcirculatory parameters in mechanically ventilated rabbits. Images were obtained using SDF imaging from the surface of the brain via craniotomy. Clear high contrast SDF images were successfully obtained. Total small-vessel density was 14.6+/-1.8 mm/mm(2), total all-vessel density was 17.9+/-1.7 mm/mm(2), DeBacker score was 12.0+/-1.6 mm(-1) and microvascular flow index was 3.0+/-0.0. This method seems to be applicable in animal studies with possibility to use SDF imaging also intraoperatively, providing unique opportunity to study cerebral microcirculation during various experimental and clinical settings.
Keywords: králíci; Rabbits; mozek; Respiration, Artificial; mikrocirkulace; Brain; Diagnostic Imaging; Animals; umělé dýchání; kraniotomie; Cerebrovascular Circulation; Microcirculation; diagnostické zobrazování; Craniotomy; zvířata; mozkový krevní oběh